Incorporating the Averse. Emulating Freemasonry? Approach to racial and hermeneutical entanglement in the Abakuá religious exercitatio - Moret-Miranda, Karo (2020)
The researcher Karo Moret-Miranda has defended a doctoral thesis dissertation, entitled “Incorporating the Averse. Emulating Freemasonry? Approach to racial and hermeneutical entanglement in the Abakuá religious exercitatio” at Pompeu Fabra University in Spain the December 20th, 2019.